Prospecção de moléculas com potencial nutracêutico em sementes de enterolobium contortisiliquum (VELL.) morong.: purificação e caracterização parcial de três inibidores de quimotripsina - Bezerra, Lady Clarissa Brito da Rocha (2010)
Leguminous seeds are main sources of food proteins for humans and animals. Other interests in these plant proteins concerning their nutraceutical properties have been raised, since many bioactive proteins, previously referred only as anti-nutritional factors, have exerted beneficial effects on health, acting as chemopreventive agents against several diseases. Among these are protease inhibitors, which play important roles in plant defense and have biological properties of interest for biotechnological applications in pharmaceutical and medical areas. This study aimed to evaluate the nutritional and nutraceutical potential of Enterolobium contortisiliquum seeds, focusing on the purification and partial characterization of chymotrypsin inhibitors and assess their antiproliferative effect against human tumor cells. E. contortisiliquum seeds are an excellent protein source, with about 50% of this macronutrient on a dry basis. The presence of protease inhibitors in high quantities suggests that these molecules may exert a nutraceutical application. Three chymotrypsin inhibitors, denominated EcCI1, EcCI2 and EcCTI were purified and partially characterized. EcCI1, EcCI2 and EcCTI show molecular weights of 17, 17 and 19 kDa, respectively. EcCI1 and EcCI2 are non-competitive inhibitors with ki of 4 x 10-8 and 2.5 x 10-8 M, respectively, while EcCTI inhibits chymotrypsin competitively with ki of 5 x 10-8 M. Only EcCTI was able to inhibit trypsin (98%). EcCI1 and EcCI2 successfully inhibited leukocyte elastase (about 70%), but EcCTI (20%). The three inhibitors slightly inhibited pancreatic elastase (about 20%) and none was able to inhibit papain. The three inhibitors have a high thermal stability (37 to 90 °C for EcCI2 and 37 to 100 °C for EcCI1 and EcCTI), pH (2 to 12) and DTT concentrations ranging from 1 to 100 mM for EcCI1 and EcCTI and from 1 to 10 mM for EcCI2. Further studies are needed to better characterize these inhibitors. None of the inhibitors promoted antiproliferative effect against four tumorigenic cell lines tested.